Sistemas de plantio, direto e convencional, na cultura do feijão 'da seca', em Viçosa, Minas Gerais - Domingos Galvão , José; V Rodrigues , Joaquim Joel; Puríssimo , Claudio (Revista Ceres, 2025)
A field test was carried out at Viçosa, Minas Gerais, Brazil, to compare no-till and conventional planted dry beans during the «dry» season. The herbicide treatments were: Roundup + Amibem Microssol + Lasso; Roundup + Amibem Microssol + Dual; and Roundup + Amibem Microssol, applied as preemergence treatments. There were no differences in weed control among herbicide treatments. The no-till yield was better than that of the conventional planted dry beans.